(3x-8)(6x+5)=0

Simple and best practice solution for (3x-8)(6x+5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-8)(6x+5)=0 equation:


Simplifying
(3x + -8)(6x + 5) = 0

Reorder the terms:
(-8 + 3x)(6x + 5) = 0

Reorder the terms:
(-8 + 3x)(5 + 6x) = 0

Multiply (-8 + 3x) * (5 + 6x)
(-8(5 + 6x) + 3x * (5 + 6x)) = 0
((5 * -8 + 6x * -8) + 3x * (5 + 6x)) = 0
((-40 + -48x) + 3x * (5 + 6x)) = 0
(-40 + -48x + (5 * 3x + 6x * 3x)) = 0
(-40 + -48x + (15x + 18x2)) = 0

Combine like terms: -48x + 15x = -33x
(-40 + -33x + 18x2) = 0

Solving
-40 + -33x + 18x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-5 + -6x)(8 + -3x) = 0

Subproblem 1

Set the factor '(-5 + -6x)' equal to zero and attempt to solve: Simplifying -5 + -6x = 0 Solving -5 + -6x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -6x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -6x = 0 + 5 -6x = 0 + 5 Combine like terms: 0 + 5 = 5 -6x = 5 Divide each side by '-6'. x = -0.8333333333 Simplifying x = -0.8333333333

Subproblem 2

Set the factor '(8 + -3x)' equal to zero and attempt to solve: Simplifying 8 + -3x = 0 Solving 8 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -3x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -3x = 0 + -8 -3x = 0 + -8 Combine like terms: 0 + -8 = -8 -3x = -8 Divide each side by '-3'. x = 2.666666667 Simplifying x = 2.666666667

Solution

x = {-0.8333333333, 2.666666667}

You can always share this solution

See similar equations:

| (8x+9)(4x-7)=0 | | x+5.2=-18.73 | | (36)(y)=14.76 | | 4.58+v=2.5 | | 8965=4 | | 11x=166 | | 3x+4=11x-6 | | 5523=0 | | 0=1111 | | 0+0=7777 | | 3y+2x=z | | 4x+9=-2x-6 | | r^2=54-3r | | -[3x+(9x+7)]=6-(3x+9) | | 10d+2dg-6d+5d-2dg= | | 2s-s+7s= | | 2x*2x+1*1-3x=5 | | 10qr-3qr+6qr-3qr= | | 14x^3+10x^2+6x= | | 2j-j+9j= | | (6Y+4)(-4Y^2-9Y+4)= | | 4+2b= | | x+5=21 | | 9n-6n+2n= | | 5-(2w-2)=3(3w-8) | | 4x^2=8+4x | | 48s+41stu-33Stu= | | 3Z-9=4Z-6 | | X^2=x+12 | | 9+3p-2p+5= | | 6X^2-18XY-7X+21Y= | | 7np-7np+4np+10np= | | 9m+9MN= | | 5x+23=13x-41 | | 2m+7n+m= | | Y-0.6Y=15 | | n^2-6n=0 | | 3r+6st+5r+3st-7st= | | 3x+2y=-9 | | -5x+3(3+2x)=7 | | 41p+37p+3pqr= | | x-7x+10=28 | | 20x+22+17x+18=90 | | 33n+32np+37n-45n+18np= | | 5x+3-4x= | | 7(2a-8)=4(2a-5) | | 2x-7y=19 | | 16+3y=5y+12 | | 4(3x-2)-4(x-2)=2 | | 5(b-6)+15=15 | | 6(7x-(7-2y+2x)+5y)= | | 14x-8=13x-10 | | MN+4MN+5MN-10MN+5MN= | | 1(x+1)=5 | | 1+4x^2=8X | | 6k+7=4+12k | | 9t^2+14-17t+6t-8t^2=0 | | X^2+6x=9 | | 10m-4(3m+7)+6m=0 | | 5x^10-4x^11=1 | | 91-7x=11x+15 | | 0=5x^10-4x^11-1 | | 10-10x=74-24x | | 2x+18=66 | | y=5x^10-4x^11-1 |

Equations solver categories